Bentuk-Bentuk Pesan Dakwah dalam Kajian Al-Qur’an - Jafar, Iftitah; Amrullah, Mudzhira Nur (Jurnal Komunikasi Islam, 2018)
This paper aims to examine the form of da’wa message in the al-Qur’an. It argues that the forms of proselytizing (da’wa) message in the Qur’an encompass; Qur’anic verses, prophetic tradition, scholar’s opinions, research results, stories, and news. The Qur’anic verses play a major role in regard with da’wa message due to its distinctive functions, namely as guidance or humankind, criterion between right and wrong, evaluation standards for other holy scriptures, and as a medium of enlightenment. ?ad?th of the Prophet Muhammad, Saw., also considered as form of da’wa message because it interpret some verses or make clarifications of ambiguities which hide in some verses. While ulema roles is as a reference for religious studies as well as stories and news constitute the proselytizing message.